Predictors for Long-Term Prognosis after Acute Coronary Syndrome - Damyan Petrov; Tatyana Vlaykova; Snezhana Tisheva (Journal of Biomedical & Clinical Research)
Cardiovascular diseases (CVD) are the leading cause of invalidity and death in developed countries. Among them, the main cause of death is coronary artery disease. In this retrospective study, 172 patients with acute coronary syndrome (STEMI, NSTEMI, UA) are included. They had been hospitalized on an emergency basis in the Cardiology Department, Invasive Sector of Prof. Dr. St. Kirkovich Hospital in Stara Zagora, and the Cardiology Hospital -Yambol between January 2009 and February 2010. We found a significant difference in the age at acute coronary syndrome (ACS) occurrence by sex: earlier manifestation was observed in men (p=0.018). The univariant regression analysis showed that elderly age (p=0.005, OR 1.024), glomerular filtration 140 pt (p